Spatio-temporal changes in degassing behavior at Stromboli volcano derived from two co-exposed SO2 camera stations - Delle Donne, Dario; Lo Coco, Eleonora; Bitetto, Marcello; La Monica, Francesco Paolo; Lacanna, Giorgio; Lages, Joao; Ripepe, Maurizio; Tamburello, Giancarlo; Aiuppa, Alessandro (Frontiers in Earth Science, 2022)
Improving volcanic gas monitoring techniques is central to better understanding open-vent, persistently degassing volcanoes. SO2 cameras are increasingly used in volcanic gas studies, but observations are commonly limited to one single camera alone viewing the volcanic plume from a specific viewing direction. Here, we report on high frequency (~0.5 Hz) systematic measurements of the SO2 flux at Stromboli, covering a 1-year long observation period (June 2017-June 2018), obtained from two permanent SO2 cameras using the same automated algorithm, but imaging the plume from two different viewing directions. The SO2 flux time-series derived from the two SO2 camera stations exhibit good match, demonstrating the robustness of the automatic SO2 camera method. Our high-temporal resolution SO2 records resolve individual strombolian explosions as transient, repetitive gas bursts produced by the sudden release of over pressurized gas pockets and scoriae. Calculations show that explosive degassing activity accounts for ~10 % of the total SO2 emission budget (dominated by quiescent degassing) during mild regular open-vent activity. We show that the temporal variations of the explosive SO2 flux go in tandem with changes in total SO2 flux and VLP seismicity, implicating some commonality in the source processes controlling quiescent degassing and explosive activity. We exploited the spatial resolution of SO2 camera to discriminate degassing at two distinct regions of the crater area, and to minimize biases due by the station position respect to the target plume. We find that the SO2 fluxes from SWCC and NEC crater areas oscillate coherently but those from the NEC are more sensitive to the changes in the volcanic intensity. We interpret this as due to preferential gas/magma channeling into the structurally weaker north-eastern portion of the crater terrace in response to increasing supply rate of buoyant, bubble-rich magma in the shallow plumbing system.